Monovalent sulfur oxoanions enable millimeter-long single-crystalline h-WO3 nanowire synthesis. Issue 16 (14th April 2020) - Zhang, Guozhu; Wang, Chen; Mizukami, Wataru; Hosomi, Takuro; Nagashima, Kazuki; Yoshida, Hideto; Nakamura, Kentaro; Takahashi, Tsunaki; Kanai, Masaki; Yasui, Takao; Aoki, Yuriko; Baba, Yoshinobu; et al.
Abstract : Monovalent sulfur oxoanions (HSO4 − and CH3 SO3 − ), rather than the previously proposed SO4 2−, significantly promote the anisotropic nanowire growth of hexagonal WO3 . Abstract : Here, we discuss a misunderstanding regarding chemical capping, which has intrinsically hindered the extension of the length of hexagonal ( h )-WO3 nanowires in previous studies. Although divalent sulfate ions (SO4 2− ) have been strongly believed to be efficient capping ions for directing anisotropic h -WO3 nanowire growth, we have found that the presence of SO4 2− is highly detrimental to the anisotropic crystal growth of the h -WO3 nanowires, and a monovalent sulfur oxoanion (HSO4 − ) rather than SO4 2− only substantially promotes the anisotropic h -WO3 nanowire growth. Ab initio electronic structure simulations revealed that the monovalent sulfur oxoanions were preferentially able to cap the sidewall plane (100) of the h -WO3 nanowires due to the lower hydration energy when compared with SO4 2− . Based on this capping strategy, using the monovalent sulfur oxoanion (CH3 SO3 − ), which cannot generate divalent sulfur oxoanions, we have successfully fabricated ultra-long h -WO3 nanowires up to the millimeter range (1.2 mm) for a wider range of precursor concentrations. We have demonstrated the feasibility of these millimeter-long h -WO3 nanowires for the electrical sensing of molecules (lung cancer biomarker: nonanal) on flexible substrates, which can be operated at room temperature with mechanical flexibility with bending cycles up to 10 4 times due to the enhanced textile effect.